BROADBAND METHOD FOR GROUP VELOCITY DISPERSION MEASUREMENTS IN THE MID-INFRARED - D. S. Klimentov; N. A. Tolstik; V. V. Dvoyrin; I. T. Sorokina (Приборы и методы измерений)
A setup for broadband measurements of dispersion parameter in optical fibers based on the Mach–Zehnder interferometer is developed. Tm-doped fiber pumped at 1.61 μm was used as a source of broadband emission, that allowed to achieve the measurement spectral range of 1700 to 2000 nm. The method is applicable for comparatively short pieces of optical fiber with lengths of less than 1 meter. The method was successfully tested for the standard telecommunication SMF-28 fiber.